Synthesis of Nd2Fe14C compound by high-energy ball-milling Nd–Fe alloy in heptane and annealing under vacuum. (3rd May 2016) - Geng, H M; Ji, Y; Feng, X Y; Zhang, J J; Ran, Z; Yan, Y; Wang, W Q; Su, F; Du, X B
Abstract: A simple synthesis route for the Nd2 Fe14 C compound with good permanent magnetic properties is presented. Being high-energy ball-milled in heptane (C7 H16 ) for 8 h, the NdFe3.5 alloy consisting of Nd2 Fe17 and Nd phases disproportionates into NdH2+ δ and α -Fe. Subsequently, NdH2+ δ decomposes when annealed from room temperature to 900 °C under vacuum, and H2 is released. Meanwhile Nd2 Fe14 C, NdC and little α -Fe phases are formed in the final product. H and C atoms come from the decomposition of heptane. Coercivity of 1.39 T and maximum magnetic energy product of 62.7 kJ m −3 have been achieved. Too short a ball-milling time results in the insufficient disproportionation of NdFe3.5 alloy and the residue of Nd2 Fe17 phase in the final product. Too long a ball-milling time results in the appearance of NdC2 and more α -Fe phases besides Nd2 Fe14 C and NdC phases. Hexane (C6 H14 ), octane (C8 H18 ) and nonane (C9 H20 ) have been proved to have a similar effect to heptane.